El papel de la Teoría General en el canon de economía - Repapis, Constantinos (Iberian Journal of the History of Economic Thought, 2020)
This paper presents in non-technical language an interpretation of the argument of The General Theory, which is the importance of effective demand and its relation to human agency. It argues that The General Theory is not only a treatise on economic theory, but also, and more importantly, a treatise on methodology, i.e. how economists should reason when dealing with the complexity of the real world. Implicit in this analysis is a distinct position on the remit of the economist and the nature of economic advice and policy. This interpretation suggests that this understanding forms a new paradigm of thinking about the economy at large, centred around the concept of uncertainty. This insight developed into a new analytical tradition in economics, the Post Keynesian School of economic thought that sees uncertainty and effective demand as the key analytical long term concepts for understanding how the economy evolves through time.